Application of the Fama-French Three Factor Model for a Five Stocks Portfolio in the US. Stock Market - Lizandra Maria Guillen Paredes (European Scientific Journal, ESJ, 2023)
In this paper, the Fama-French three-factor model was applied to explore how to construct an optimized portfolio and achieve maximum returns, by using historical stock data for various industries, in the period from 2002 to 2022. The findings of this paper can be useful for first-time investors in various financial markets.